Factors that influence women's engagement with breastfeeding support: A qualitative evidence synthesis - Theresa Bengough; Shoba Dawson; Hui‐Lin Cheng; Alison McFadden; Anna Gavine; Rebecca Rees; Emma Sacks; Karin Hannes (Wiley, 2022)
Abstract Breastfeeding is an integral part of early childhood interventions as it can prevent serious childhood and maternal illnesses. For breastfeeding support programmes to be effective, a better understanding of contextual factors that influence women's engagement and satisfaction with these programmes is needed. The aim of this synthesis is to suggest strategies to increase the level of satisfaction with support programmes and to better match the expectations and needs of women. We systematically searched for studies that used qualitative methods for data collection and analysis and that focused on women's experiences and perceptions regarding breastfeeding support programmes. We applied a maximum variation purposive sampling strategy and used thematic analysis. We assessed the methodological quality of the studies using a modified version of the CASP tool and assessed our confidence in the findings using the GRADE‐CERQual approach. We included 51 studies of which we sampled 22 for in‐depth analysis. Our sampled studies described the experiences of women with formal breastfeeding support by health care professionals in a hospital setting and informal support as for instance from community support groups. Our findings illustrate that the current models of breastfeeding support are dependent on a variety of contextual factors encouraging and supporting women to initiate and continue breastfeeding. They further highlight the relevance of providing different forms of support based on socio‐cultural norms and personal backgrounds of women, especially if the support is one‐on‐one. Feeding decisions of women are situated within a woman's personal situation and may require diverse forms of support.